2020
DOI: 10.1002/ijfe.2256
|View full text |Cite
|
Sign up to set email alerts
|

The impact of bank ownership on lending behavior: Evidence from the 2008–2009 financial crisis

Abstract: This paper investigates the lending behavior of banks with different ownership types (domestic-private, foreign, and government-owned) during normal and financial crisis periods. Using panel data for the period 2004-2013, our results indicate that the 2008-2009 crisis caused a negative shock to banking sector loan growth rates which was considerably higher during 2008 compared to 2009. Although loan supply decreased during the crisis, there were differences under different ownership types and between high and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In this case, if the government does not protect local investors, the monopoly of foreign ownership of banking shares in Indonesia will continue to increase. [13] Even though the beneficial value of monopoly activities can contribute more to the stability of the national economic system and boost development in the financial sector, the value of distributive justice, which should be the main principle of this policy, needs to be addressed. Suppose the government needs to review this policy.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In this case, if the government does not protect local investors, the monopoly of foreign ownership of banking shares in Indonesia will continue to increase. [13] Even though the beneficial value of monopoly activities can contribute more to the stability of the national economic system and boost development in the financial sector, the value of distributive justice, which should be the main principle of this policy, needs to be addressed. Suppose the government needs to review this policy.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Recently, Fukuyama and Tan (2020) stated that management and reduction of risk levels will not only be good for stability, but may also enhance efficiency because the banking sector plays a major part in the country's economy, healthy progress, and sustainable development. Haldarov, Asteriou, and Trachanas (2020) have expressed that the 2008 financial crisis resulted in the severe instability of banking systems. Additionally, Le, Ševi c, Tzeremes, and Ngo (2020) reported that several problems and challenges emerged in the banking sector's stability and efficiency components in the wake of the financial crisis.…”
mentioning
confidence: 99%